Diseño metodológico en la creación del manual para la implementación a normas NIIF en la estación de servicios Condor - Yondó Antioquia (2019)
This article leaves for consideration the result of the study conducted during a process of implementation of IFRS standards developed by the research group DIANOIA of the Technological Units of Santander Regional Barrancabermeja with the service company EDS CONDOR located in Yondó Antioquia. The content is the product of the experiences found, and is developed trying to deepen in those topics in which it was observed more difficulty in the process of implementation of the standards. The implementation of this project allows the identification of the needs of service stations and specifically the EDS CONDOR in Yondó Antioquia, regarding the implementation of IFRS standards in its current accounting process, allowing the definition of the methodology for the implementation of a manual that guides the logbook of the integral accounting system and thus be able to make important decisions by its owner partners.